Changes 2006–2010 in the list of Finnish insects - Silfverberg, Hans (Entomologica Fennica, 2012)
During the period 142 species have been deleted from the list of Finnish insects, and 1,223 species have been added to it. At the end of year 2010 a total of 21,613 insect species were known from Finland.